2020
DOI: 10.1016/j.molmet.2020.101062
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 5 regulates interleukin 6 secretion and insulin action in skeletal muscle

Abstract: Objective Physical exercise training is associated with increased glucose uptake in skeletal muscle and improved glycemic control. HDAC5, a class IIa histone deacetylase, has been shown to regulate transcription of the insulin-responsive glucose transporter GLUT4 in cultured muscle cells. In this study, we analyzed the contribution of HDAC5 to the transcriptional network in muscle and the beneficial effect of muscle contraction and regular exercise on glucose metabolism. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Lenoir et al found an increase in insulin-producing b-cell mass in the pancreas of HDAC5-knockout mice while a decrease in HDAC5-overexpressed mice, demonstrating a suppressing role of HDAC5 in insulin production (35). Such an effect on insulin action was also observed in muscle cells (36,37). Studies have shown that insulin resistance is associated with both GSD and central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Lenoir et al found an increase in insulin-producing b-cell mass in the pancreas of HDAC5-knockout mice while a decrease in HDAC5-overexpressed mice, demonstrating a suppressing role of HDAC5 in insulin production (35). Such an effect on insulin action was also observed in muscle cells (36,37). Studies have shown that insulin resistance is associated with both GSD and central obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic regulation might also be involved in ELSM-induced gene regulation. Klymenk O. et al [ 64 ] reported that ELSM-induced interleukin 6 (IL6) transcription was enhanced in histone deacetylase 5(HDAC5)-deficient C2C12 myotubes. Recent studies have shown that EV-derived microRNAs contribute to cardioprotection by acting as anti-apoptotic mediators [ 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In PRMT1-deficent mice, IL-6 expression in the liver was decreased, suggesting that PRMT1 is involved in the regulation of IL-6 expression (Zhao et al, 2019). Klymenko et al (Klymenko et al, 2020) found that HDAC5 can negatively regulate IL-6 gene expression and then affect glucose uptake in skeletal muscle cells. By electrically stimulating C2C12 cells to generate a muscle contraction model, it was found that IL-6 expression in HDAC5-deficient myocytes was higher than that in wildtype cells, suggesting that HDAC5 was also involved in the regulation of exercise-induced IL-6 expression.…”
Section: The Mechanism Underlying Exerciseinduced Expression Of Myokinesmentioning
confidence: 99%